On Cultural Politics in Special Education: Is Much of It Justifiable?. (September 2019) - Kauffman, James M.; Anastasiou, Dimitris
This article examines the nature of cultural politics in special education, specifically conceptual and methodological issues, as well as political implications related to minority disproportionate representation in disability identification rates. The implication of cultural politics is a focus on the hypothesis that minority disproportionate representation of minorities in special education is definitely a result of racial discrimination, accompanied by criticism of recently contested research suggesting their underrepresentation after controlling for confounds. Cultural politics has practical consequences, such as recently proposed policy changes that extract scarce sources from the education of students already identified as having disabilities. Special education is urged to focus on effective instruction and on three things in addressing disproportionality: (a) close adherence to facts and the best corroborating evidence; (b) explanations and theories that are testable, confirmable, and refutable on the basis of reliable data; and (c) clear and rational arguments that can be followed by policy makers. Carefully designed research to further explore this issue should recognize that (a) disproportionality is, by definition, a quantitative phenomenon and (b) replication and refinement of recent studies are needed.